Developing optimal power flow and DER control schemes for lowering system losses - Ng, Keng Boon (2016)
There is a growing demand for sustainable energy and concerns for reliability and quality of power supply due to aging infrastructure of electricity transmission and distribution network. The introduction of microgrid (MG) can be used to mitigate the issues. It is a small scale and localized electricity supply system and is the most popular form of distributed generation. It has high flexibility and is able to run in both grid connected and autonomous operation. The integration of Distributed Energy Resources (DERs) made it possible to supply the load without the main grid. However, the integration of DERs poses a conundrum for the Energy Management System (EMS). The traditional energy management system had to be re-evaluated. One such area is the Optimal Power Flow (OPF). The objectives of this report are to propose a power loss reduction plan for the MG, conduct a research on OPF and study the effectiveness of the algorithm. In this report, Particle Swarm Optimization (PSO) is tested using IEEE-30 and IEEE-118 bus network. The objective functions considered in this simulation are minimizing system losses and maintaining bus voltage at nominal value. The report also studies the advantageous and disadvantageous of conventional and heuristic optimization approach. The existing OPF solver based on Quadratic Programming (QP) in Clean Energy Research Lab (CERL) is compared with the PSO and is tested with the microgrid system in Clean Energy Research Laboratory. The decision variables that are used in the microgrid system are the capacitor banks and tap changers. The effectiveness of the algorithm and the decision variables that are used to reduce the system losses is being analyzed.